Impact of exercise modalities on blood pressure control in hypertensive patients: A narrative review - Abderrahmen, Tahchi; Chaouki, Hassen Ahmed; Mehamed, Ghessier; Khaled, Kharchi Amir; Rachid, Brahimi (International journal of health sciences, 2024)
Hypertension poses a significant health burden, necessitating effective interventions to manage blood pressure and mitigate associated cardiovascular risks. Exercise has emerged as a cornerstone non-pharmacological strategy in the management of hypertension. This comprehensive review synthesizes current evidence regarding the impact of various exercise modalities on blood pressure regulation in hypertensive individuals. The review commences by elucidating the physiological mechanisms underpinning exercise-induced blood pressure alterations, highlighting factors influencing blood pressure responses during different exercises. It delineates the differential impacts of aerobic and resistance training, examining their effectiveness in blood pressure reduction among diverse populations, considering age, fitness levels, and comorbidities. Moreover, the review explores the emerging prominence of high-intensity interval training (HIIT), showcasing its unique effects on blood pressure regulation and cardiorespiratory fitness improvement compared to traditional continuous aerobic exercises. Additionally, alternative mind-body exercises, including tai chi, qigong, and mindfulness-based interventions, are investigated for their potential to influence blood pressure levels among hypertensive populations. Furthermore, the review identifies novel exercise approaches such as deep breathing exercises and multi-modal isometric exercise training (MIET) as promising strategies for blood pressure control in hypertensive individuals, emphasizing their potential benefits and implications for tailored exercise prescriptions.